EFL Students’ Perception in Using Duolingo for Developing Speaking Ability - Humairoh, Siti; Martriwati (PROJECT (Professional Journal of English Education), 2025)
English-speaking ability is an essential skill for EFL students to communicate effectively; however, many students face challenges such as limited vocabulary, lack of motivation, and low self-confidence. Therefore, the study "EFL Students’ Perception in Using Duolingo for Developing Speaking Ability" aims to analyze students' perceptions of using Duolingo to improve their speaking skills, focusing on how the application's features assist in speaking development and its effectiveness in English language learning at senior high schools in the Greater Jakarta area. This research using quantitative method, with data collected through a Likert-scale questionnaire administered to 25% of 187 randomly selected students. The results indicate that students have a positive perception of Duolingo due to features such as a reward system, learning reminders, and game-based multimedia content, which enhance motivation, confidence, learning flexibility, and active participation in speaking. However, challenges such as limited vocabulary and fear of making mistakes still persist, suggesting that while Duolingo is an effective learning tool, its use should be supplemented with conventional teaching methods for optimal improvement in English-speaking skills.